1997
DOI: 10.1172/jci119465
|View full text |Cite
|
Sign up to set email alerts
|

IFN-gamma potentiates atherosclerosis in ApoE knock-out mice.

Abstract: The early colocalization of T cells and the potent immunostimulatory cytokine IFN-␥ to atherosclerotic lesions suggest that the immune system contributes to atherogenesis. Since mice with a targeted disruption of the apoE gene (apoE 0 mice) develop profound atherosclerosis, we examined the role of IFN-␥ in this process. First, the presence of CD4 ϩ and CD8 ϩ cells, which secrete lesional IFN-␥ , was documented in apoE 0 atheromata. Then, the apoE 0 mice were crossed with IFN-␥ receptor (IFN ␥ R) 0 mice to gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

32
530
6
16

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 799 publications
(590 citation statements)
references
References 50 publications
32
530
6
16
Order By: Relevance
“…Th1 adaptive responses, and Th1 cytokines in particular have been shown to play a key role in promoting atherogenesis (17,(35)(36)(37). In contrast, we now demonstrate that immunization with MDA-LDL directly triggers an antigen-specific Th2 response that is associated with an atheroprotective effect.…”
Section: Discussionmentioning
confidence: 56%
“…Th1 adaptive responses, and Th1 cytokines in particular have been shown to play a key role in promoting atherogenesis (17,(35)(36)(37). In contrast, we now demonstrate that immunization with MDA-LDL directly triggers an antigen-specific Th2 response that is associated with an atheroprotective effect.…”
Section: Discussionmentioning
confidence: 56%
“…IFN-␥ plays a role in the development of atherosclerosis, both as a consequence of its effects on plaque progression/stability [25,26] and via its negative impact on blood lipid trafficking (for review see Leon and Zuckerman [27]). In our present study, treatment reduced the plasma concentration of IFN-␥ by more than 90%.…”
Section: Discussionmentioning
confidence: 99%
“…IFN-␥ upregulates IL-1 and TNF-␣ production, cytokines that are pivotal protein mediators of inflammation 24 and upregulate adhesion molecule expression on vascular endothelial cells. 25,26 Gupta et al, 27 using compound apoE-deficient, IFN-␥ receptor-deficient mice, showed that IFN-␥ can potentiate murine atherosclerosis through both local effects in the arterial wall and systemic effects on plasma lipoproteins. Conversely, Th2-derived IL-4 inhibits proinflammatory cytokine release.…”
Section: Discussionmentioning
confidence: 99%